Effects of lighting regimes on performance, pineal melanopsin expression and melatonin content in native laying hens aged from 19 to 34 weeks - A.L. Geng (Elsevier, 2022)
ABSTRACT: Melanopsin, a key light sensitive pigment, plays an important role in the regulation of bio-rhythm and photo-adaptation in poultry. This study aimed to investigate the effects of different lighting regimes on performance, pineal melanopsin expression and melatonin content in a native chicken, Beijing You Chicken (BYC) aged from 19 to 34 wk. A total of 900 nineteen-wk-old BYC female chicken having no significant body weight differences were randomly allocated to 3 groups with 3 replicates each, 100 birds each replicate, reared in individually lit floor pens with separate outdoor areas. Three different lighting regimes were used, including continuous 16 h (16L:8D, 6:00–22:00) for group 1, intermittent 16 h (12L:2D:4L:6D, 6:00–18:00, 20:00–24:00) for group 2, and continuous 12 h (12L:12D, 6:00–18:00) for group 3, respectively. The performance was measured for 19 to 34 wk. Serum melatonin (Mel), prolactin (Prl), luteinizing hormone (LH), and 17-beta estradiol (E2) contents were measured at 24 wk, 29 wk, and 34 wk of age, the relative expression of pineal melanopsin gene (Opn4 mRNA) was measured on 1 d at 9:00, 13:00, 17:00, 21:00, 1:00, and 5:00 at 29 wk of age, and at the end of 29 wk and 34 wk. The results showed that the egg mass, egg-laying rate, and feed egg ratio of BYC were not affected by lighting regimes for 19 to 34 wk (P > 0.05), except for the average feed intake (AFI) (P < 0.05). The AFI in the 12L:12D group was significantly higher than that in the 16L:8D group (P < 0.05), but had no difference with that in the 12L:2D:4L:6D group. The pineal Opn4 mRNA level was significantly upregulated in the 12L:2D:4L:6D group and downregulated in the 12L:12D group when compared with 16L:8D group at 29 and 34 wks of age (P < 0.05). The Mel content in the 16L:8D group was lower than that in the other 2 groups at 29 wk of age (P < 0.05), there was no difference in Mel content between 16L:8D group and 12L:2D:4L:6D group at 34 wk of age (P > 0.05). The present study suggested that the pineal melanopsin expression of the birds in the intermittent 16 h lighting group was higher than in the continuous 16 h and 12 h lighting group, and a significant negative correlation was found between melanopsin expression and Mel content at 34 wk of age, which may interact to promote the photo-adaptation of the native chicken and affect the future laying performance.